2012
DOI: 10.3892/etm.2012.673
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between surfactant protein B mRNA expression and neonatal respiratory distress syndrome

Abstract: The aim of this study was to investigate whether surfactant-associated protein B (SP-B) mRNA deficiency is involved in the pathogenesis of neonatal respiratory distress syndrome (RDS). A total of 60 unrelated neonates who died of RDS were recruited as the RDS group and subgrouped into a ≤32-, a 32–36+6- and a ≥37-week group (n=20 per group) on the basis of gestational age. In addition, 60 neonates who succumbed to other diseases were enrolled as controls. The lung tissues were collected within 30 min after dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Among them, SP-A and SP-D participate in host defense in the lung, whereas SP-B and SP-C contribute to the surface tension-lowering activity (Avery, 2000). It has been confirmed that SP-B and SP-C protein deficiencies are associated with the pathogenesis of neonatal respiratory distress syndrome (RDS) (Yin et al, 2012;Danlois et al, 2000). SP-C, a small lipopeptide of 4.5 kDa with 35 residues, exclusively produced in lungs by the AEC II cells, is believed to promote and stabilize membrane-interface contacts and to facilitate lipid exchange between lipid layers (Glasser et al, 2001;Lukovic et al, 2012).…”
Section: Introductionmentioning
confidence: 91%
“…Among them, SP-A and SP-D participate in host defense in the lung, whereas SP-B and SP-C contribute to the surface tension-lowering activity (Avery, 2000). It has been confirmed that SP-B and SP-C protein deficiencies are associated with the pathogenesis of neonatal respiratory distress syndrome (RDS) (Yin et al, 2012;Danlois et al, 2000). SP-C, a small lipopeptide of 4.5 kDa with 35 residues, exclusively produced in lungs by the AEC II cells, is believed to promote and stabilize membrane-interface contacts and to facilitate lipid exchange between lipid layers (Glasser et al, 2001;Lukovic et al, 2012).…”
Section: Introductionmentioning
confidence: 91%